Design of a double-decker coordination cage revisited to make new cages and exemplify ligand isomerism - Samantray, Sagarika; Bandi, Sreenivasulu; Chand, Dillip K. (Beilstein Journal of Organic Chemistry, 2019)
The complexation study of cis-protected and bare palladium(II) components with a new tridentate ligand, i.e., pyridine-3,5-diylbis(methylene) dinicotinate (L1) is the focus of this work. Complexation of cis-Pd(tmeda)(NO3)2 with L1 at a 1:1 or 3:2 ratio produced [Pd(tmeda)(L1)](NO3)2 (1a). The reaction mixture obtained at 3:2 ratio upon prolonged heating, produced a small amount of [Pd3(tmeda)3(L1)2](NO3)6 (2a). Complexation of Pd(NO3)2 with L1 at a 1:2 or 3:4 ratios afforded [Pd(L1)2](NO3)2 (3a) and [(NO3)2@Pd3(L1)4](NO3)4 (4a), respectively. The encapsulated NO3– ions of 4a undergo anion exchange with halides (F–, Cl– and Br– but not with I–) to form [(X)2@Pd3(L1)4](NO3)4 5a–7a. The coordination behaviour of ligand L1 and some dynamic properties of these complexes are compared with a set of known complexes prepared using the regioisomeric ligand bis(pyridin-3-ylmethyl)pyridine-3,5-dicarboxylate (L2). Importantly, a ligand isomerism phenomenon is claimed by considering complexes prepared from L1 and L2.
Keywords: anion binding; double-decker cage; ligand isomerism; macrocycles; palladium; self-assembly; supramolecular